Relevance of Cash Flow Information in Long-Term Investment Assessment: Time Value of Money Perspective - Nurul Khotimah; Muchriana Muchran; Uswatun Khasanah (IECON: International Economics and Business Conference, 2025)
This study aims to examine the relevance of cash flow information in the long-term investment assessment process by considering the time value of money perspective. The study was conducted at PT Mahaka Media Tbk during the period 2020–2022, using consolidated financial statement data covering cash flows from operating, investing, and financing activities. The analysis methods used include cash flow evaluation, capital expenditure (CAPEX) calculation, and free cash flow (FCF) to measure the company's ability to finance its long-term investments internally. The results of the study show that PT Mahaka Media Tbk consistently experiences negative operating cash flow, which has an impact on the company's dependence on external funding to support investment. This condition affects the present value of future cash flows due to higher capital costs, thus reducing the feasibility of long-term investment. This finding emphasizes the importance of integrating cash flow information and the concept of the time value of money in investment decision making, in order to ensure that investment projects can generate added value sustainably. This study provides practical implications for financial management in formulating more effective cash flow and investment management strategies.